Discovery of Nuclear-Encoded Genes for the Neurotoxin Saxitoxin in Dinoflagellates - Stüken, Anke; Orr, Russell J. S.; Kellmann, Ralf; Murray, Shauna A.; Neilan, Brett A.; Jakobsen, Kjetill S. (PLOS ONE, 2011)
Saxitoxin is a potent neurotoxin that occurs in aquatic environments worldwide. Ingestion of vector species can lead to paralytic shellfish poisoning, a severe human illness that may lead to paralysis and death. In freshwaters, the toxin is produced by prokaryotic cyanobacteria; in marine waters, it is associated with eukaryotic dinoflagellates. However, several studies suggest that saxitoxin is not produced by dinoflagellates themselves, but by co-cultured bacteria. Here, we show that genes required for saxitoxin synthesis are encoded in the nuclear genomes of dinoflagellates. We sequenced >1.2×106 mRNA transcripts from the two saxitoxin-producing dinoflagellate strains Alexandrium fundyense CCMP1719 and A. minutum CCMP113 using high-throughput sequencing technology. In addition, we used in silico transcriptome analyses, RACE, qPCR and conventional PCR coupled with Sanger sequencing. These approaches successfully identified genes required for saxitoxin-synthesis in the two transcriptomes. We focused on sxtA, the unique starting gene of saxitoxin synthesis, and show that the dinoflagellate transcripts of sxtA have the same domain structure as the cyanobacterial sxtA genes. But, in contrast to the bacterial homologs, the dinoflagellate transcripts are monocistronic, have a higher GC content, occur in multiple copies, contain typical dinoflagellate spliced-leader sequences and eukaryotic polyA-tails. Further, we investigated 28 saxitoxin-producing and non-producing dinoflagellate strains from six different genera for the presence of genomic sxtA homologs. Our results show very good agreement between the presence of sxtA and saxitoxin-synthesis, except in three strains of A. tamarense, for which we amplified sxtA, but did not detect the toxin. Our work opens for possibilities to develop molecular tools to detect saxitoxin-producing dinoflagellates in the environment.